Get smart – technological innovations in endodontics. Part 1: 3D imaging, 3D treatment planning and guided endodontics. (2nd June 2021) - Shah, Pratik Kamalkant; Zhang, Qianni; Chong, Bun San
Abstract : Endodontic treatment can be technically challenging, requiring a high level of clinical precision and skill to avoid mishaps, to achieve a quality result and to ensure a favourable outcome. Understandably, dentists vary in competency and ability to manage challenging endodontic cases. Coupled with patients' desire to retain their natural dentition, the demand for endodontic treatment exceeds service provision. Secondary and tertiary care providers are inundated with referrals. Access to privately funded services may also be restricted due to availability and locality. The scientific and technological revolution in healthcare has benefited many medical and dental disciplines, including endodontics: solutions may be found within these technological innovations to improve and facilitate the delivery of endodontic care. CPD/Clinical Relevance: Technological innovations can contribute and facilitate the assessment, management and treatment of challenging endodontic cases in everyday clinical practice.